The Implementation of Information Technology to Enhance Teaching and Learning Effectiveness in Higher Education - Desfita Eka Putri (Civiliza Publishing, Indonesia., 2025)
This study examines the implementation of information technology (IT) in higher education and its role in enhancing teaching and learning effectiveness amid accelerated digital transformation. Although IT is widely promoted as a catalyst for improving instructional quality, empirical evidence shows that its impact remains inconsistent across institutional and pedagogical contexts. Accordingly, this research aims to analyze how and under what conditions IT implementation contributes to effective teaching and learning in higher education. The study employs a mixed-methods explanatory design, combining quantitative survey data from lecturers and undergraduate students with qualitative interviews involving academic staff and institutional managers. Quantitative data were analyzed using inferential statistical techniques to identify relationships between IT integration, pedagogical practices, and learning effectiveness, while qualitative data were thematically analyzed to explain underlying mechanisms and contextual factors. The findings reveal that IT implementation significantly enhances learning effectiveness only when it is pedagogically integrated, supported by lecturers’ digital pedagogical competence, and reinforced by coherent institutional support systems. Conversely, technology adoption that is superficial or infrastructure-driven yields limited educational benefits. The study concludes that IT functions as a mediating infrastructure rather than an autonomous driver of educational quality. Its primary contribution lies in advancing a conditional and systemic model of technology-enhanced learning that integrates pedagogical, human, and organizational dimensions, thereby offering theoretically grounded and empirically informed insights for higher education policy, practice, and future research.